颈动脉脉搏波传导速度及血清Lp-PLA2、NRG-1与伴高血压的急性缺血性卒中的关系The Relationship between Carotid Pulse Wave Velocity, Serum Lp-PLA2, NRG-1, and Acute Ischemic Stroke with Hypertension - 王赟,米亚儒,邓荷萍,张博(WANG Yun, MI Yaru, DENG Heping, ZHANG Bo) (Zhongguo cuzhong zazhi)
目的 探讨颈动脉脉搏波传导速度（pulse wave velocity，PWV）及血清脂蛋白相关磷脂酶A2（lipoprotein-associated phospholipase A2，Lp-PLA2）、神经调节蛋白-1（neuregulin-1，NRG-1）与伴高血压的大动脉粥样硬化（large artery atherosclerosis，LAA）型急性缺血性卒中（acute ischemic stroke，AIS）的关系。 方法 前瞻性连续纳入河北医科大学第三医院2022年8月—2024年8月收治的伴高血压AIS患者作为研究组，同期收治的单纯高血压患者作为对照组。对比研究组和对照组患者的基线资料；利用logistic回归模型进行高血压合并AIS的多因素分析。根据NIHSS评分将研究组的患者分为神经功能缺损轻度（NIHSS评分＜5分）、中度（5分≤NIHSS评分≤15分）及重度（NIHSS评分＞15分）组，并对比3组患者的基线资料；利用Pearson相关系数分析颈动脉收缩期开始时脉搏波传导速度（pulse wave velocity at the beginning of systole，PWV-BS）、收缩期结束时脉搏波传导速度（pulse wave velocity at the end of systole，PWV-ES）、Lp-PLA2、NRG-1与NIHSS评分的相关性；利用logistic回归模型进行AIS伴高血压患者神经功能缺损严重程度的多因素分析。 结果 研究组共纳入172例AIS伴高血压患者，对照组共纳入103例单纯高血压患者。logistic回归分析显示，研究组的Lp-PLA2（OR 1.031，95%CI 1.017～1.045，P＜0.001）、PWV-BS（OR 1.947，95%CI 1.232～3.079，P=0.004）及PWV-ES（OR 2.218，95%CI 1.567～3.138，P＜0.001）水平高于对照组，而NRG-1（OR 0.994，95%CI 0.990～0.997，P＜0.001）水平低于对照组。研究组172例AIS伴高血压患者中，轻度组68例，中度组81例，重度组23例。Pearson相关性分析显示，PWV-BS（r=0.631，P＜0.001）、PWV-ES（r=0.599，P＜0.001）、Lp-PLA2（r=0.489，P＜0.001）水平均与NIHSS评分呈正相关，而NRG-1与NIHSS评分呈负相关（r=-0.485，P＜0.001）。logistic回归分析显示，中度组和重度组的高血压病程（OR 40.469，95%CI 2.915～561.898，P=0.006；OR 160.155，95%CI 10.357～2476.616，P＜0.001）长于轻度组，Lp-PLA2（OR 1.154，95%CI 1.039～1.282，P=0.007；OR 1.191，95%CI 1.069～1.328，P=0.002）、PWV-BS（OR 23.275，95%CI 1.135～477.237，P=0.041；OR 79.267，95%CI 3.158～1989.561，P=0.008）和PWV-ES（OR 99.259，95%CI 3.367～2926.000，P=0.008；OR 203.017，95%CI 6.212～6634.497，P=0.003）水平均高于轻度组，而NRG-1（OR 0.980，95%CI 0.964～0.996，P=0.014；OR 0.975，95%CI 0.957～0.993，P=0.007）水平低于轻度组。 结论 伴高血压AIS患者的PWV-BS、PWV-ES及Lp-PLA2水平明显升高，NRG-1水平明显降低；高血压病程，Lp-PLA2、PWV-BS、PWV-ES及NRG-1水平与伴高血压AIS患者神经功能缺损的严重程度有关。Abstract: Objective To investigate the relationship between carotid pulse wave velocity (PWV), serum lipoprotein-associated phospholipase (Lp-PL) A2, and neuregulin-1 (NRG-1) with large artery atherosclerosis (LAA)-type acute ischemic stroke (AIS) with hypertension. Methods AIS patients with hypertension admitted to the Hebei Medical University Third Hospital from August 2022 to August 2024 were prospectively and consecutively included as the study group, and patients with hypertension alone were selected as the control group. The baseline data of patients in the study group and the control group were compared. The logistic regression model was used for multivariate analysis of hypertension combined with AIS. In the study group, patients were divided into mild (NIHSS score<5), moderate (5≤NIHSS score≤15), and severe (NIHSS score>15) groups based on neurological deficits, as classified by NIHSS score. The baseline data of patients in the three groups were then compared. The Pearson correlation coefficient was used to analyze the correlation between pulse wave velocity at the beginning of systole (PWV-BS), pulse wave velocity at the end of systole (PWV-ES), Lp-PLA2, NRG-1, and NIHSS score. The logistic regression model was used for multivariate analysis of the severity of neurological deficit in AIS patients with hypertension. Results A total of 172 AIS patients with hypertension were included in the study group and 103 patients with hypertension alone were included in the control group. The multivariate analysis of logistic regression model showed that the levels of Lp-PLA2 (OR 1.031, 95%CI 1.017-1.045, P＜0.001), PWV-BS (OR 1.947, 95%CI 1.232-3.079, P=0.004), and PWV-ES (OR 2.218, 95%CI 1.567-3.138, P＜0.001) in the study group were higher than those in the control group, while the level of NRG-1 (OR 0.994, 95%CI 0.990-0.997, P＜0.001) was lower than that in the control group. Among the 172 AIS patients with hypertension in the study group, there were 68 patients in the mild group, 81 patients in the moderate group, and 23 patients in the severe group. Pearson correlation analysis showed that PWV-BS (r=0.631, P＜0.001), PWV-ES (r=0.599, P＜0.001), and Lp-PLA2 (r=0.489, P＜0.001) were positively correlated with NIHSS score, while NRG-1 was negatively correlated with NIHSS score (r=-0.485, P＜0.001). Multivariate analysis of the logistic regression model showed that the duration of hypertension in the moderate and severe groups (OR 40.469, 95%CI 2.915-561.898, P=0.006; OR 160.155, 95%CI 10.357-2476.616, P＜0.001), Lp-PLA2 (OR 1.154, 95%CI 1.039-1.282, P=0.007; OR 1.191, 95%CI 1.069-1.328, P=0.002), PWV-BS (OR 23.275, 95%CI 1.135-477.237, P=0.041; OR 79.267, 95%CI 3.158-1989.561, P=0.008), and PWV-ES (OR 99.259, 95%CI 3.367-2926.000, P=0.008; OR 203.017, 95%CI 6.212-6634.497, P=0.003) were higher than those in the mild group, while the level of NRG-1 (OR 0.980, 95%CI 0.964-0.996, P=0.014; OR 0.975, 95%CI 0.957-0.993, P=0.007) was lower than that in the mild group. Conclusions PWV-BS, PWV-ES, and Lp-PLA2 levels were significantly higher and NRG-1 level was significantly lower in AIS patients with hypertension. The duration of hypertension, and the levels of Lp-PLA2, PWV-BS, PWV-ES and NRG-1 were related to the severity of neurological deficits in AIS patients with hypertension.